Validation of Surface Elevation from TanDEM-X Digital Elevation Models of Devon Island Ice Cap, Canadian High Arctic - Bernard-Grand'Maison, Claire (Université d'Ottawa / University of Ottawa, 2019)
Digital elevation models (DEMs) generated by the TanDEM-X mission from synthetic aperture radar interferometry (InSAR) provide an excellent potential resource to study the geodetic mass balance of glaciers. However, they typically suffer from a negative bias in surface elevations on glacierized terrain due to penetration of radar waves into the snowpack and firn. In this thesis, TanDEM-X DEMs from 2010 to 2018 over Devon Island Ice Cap (DIC), Canadian High Arctic, are validated using independent surface elevation datasets from ArcticDEM, IceBridge laser altimetry and ground GPS transects. In agreement with previous studies using TanDEM-X DEMs, the bias is most significant in the percolation and saturation zones (i.e., accumulation area), where volume scattering and loss of interferometric coherence is greatest compared to the bare ice zone. The average elevation bias on DIC is -2.74 ±0.25 m, which should be accounted for in error budgets for geodetic mass balance estimates to be reliable.
Keywords: Devon Island Ice Cap; Glaciology; TanDEM-X; Digital Elevation Model; Canadian Arctic; Glacier Mass Balance